Respiratory physiotherapy : an on-call survival guide - Harden, Beverley; ScienceDirect eBooks (Edinburgh ; New York : Churchill Livingstone, 2009)
The second edition of RESPIRATORY PHYSIOTHERAPY (formerly EMERGENCY PHYSIOTHERAPY) continues to be a highly accessible and convenient guide which brings the insight of clinical experts in the field to the fingertips of the busy physiotherapist who are often exposed to challenging and stressful situations. Beverley Harden is now joined by a team of 5 additional Editors and the new edition has been completely revamped. It looks at assessment, management of and calls to specific areas while presenting key information in tables, bullets and summaries for quick reference on the ward. Case studies that cover common emergency situationsSelf-assessment questions which offer the reader verification of their comprehension and clinical reasoning skillsA-Z of treatment techniquesAppendices including normal values and common drugs used in critical care areas so that essential information is always at hand.
Learning for and from being on call / Jane Cross -- On call preparation / Mary-Ann Broad, Carole Jones -- Respiratory assessment / Matthew Quint, Sandy Thomas -- Paediatric specifics / Fiona Roberts -- Chest x-ray interpretation / Stephen Harden -- The management of sputum retention / Ruth Wakeman -- The management of volume loss / Bernadette Henderson, Nell Clotworthy -- The management of increased work of breathing / Alison Aldridge -- Management of respiratory failure / Sarah EJ Keilty -- Calls to intensive care / Rachel Devlin -- Calls to paediatric intensive care / Elaine Dhouieb -- Calls to a medical unit / Elizabeth Thomas -- Calls to the surgical unit / Val Ball -- Calls to the neurosurgical unit / Lorraine Clapham -- Call to the cardiothoracic unit / Angela Kell -- Calls to the oncology unit / Irelna Kruger -- Calls to the paediatric unit / Paul Ritson -- Calls to the neonatal unit / Alison Carter -- Respiratory physiotherapy treatments / Alison Draper, Paul Ritson.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Respiratory emergencies; Respiratory organs -- Diseases -- Physical therapy; Respiratory emergencies; Respiratory organs -- Diseases -- Physical therapy; Emergency Treatment -- methods -- Handbooks; Respiratory Therapy -- methods -- Handbooks; Physical Therapy Modalities -- Handbooks; Electronic books